(untitled) (Journal of Global Humanities and Social Sciences, 2025)
Machine learning has great potential in reducing product and service costs, speeding up business processes and serving customers better. In this era of unprecedented development of technology, as one of the most important application fields, machine learning has also been widely used in financial investment. In view of this, this paper briefly discusses the connotation of machine learning, introduces the application of machine learning in financial investment, and lays the foundation for the future development of financial industry.